Ecological and evolutionary relative importance to total abundance and mean size changes of an artificial phytoplankton community in response to high CO2 after 80,186 and 288 days - Giannina S I Hattich; Luisa Listmann; Thorsten B H Reusch; Birte Matthiessen; Jonathan N Havenhand (PANGAEA, 2022)
This dataset includes information specific to the Eco-Evo assay applied to a long-term community selection experiment after 80,186, and 288 days. The community contained Emiliania huxleyi and Chaetoceros affinis (details about Species and genotypes used can be found in doi:10.1098/rsbl.2016.0774 ). The long-term community selection phase to ambient and high CO2 (400 and 1250ppm, respectively) started on the 10th of January 2017, details about the sorting phase in semi-continuous batch cycles can be found in doi:10.1594/PANGAEA.887780 . Here, the raw data from the subsequent Eco-Evo assay are presented, as well as the calculated relative importance of species and genotype sorting. The first eco-evo Assay (after 80 days) previously served to validate the new method (https://doi.org/10.1111/1365-2435.13923) and Abundance (column 8) of Time 80 (first 25 rows) and the calculated relative contribution to total changes of that timepoint (column 28- first 4 rows) are also included in the previous dataset (https://doi.org/10.1594/PANGAEA.896220). Abundance-weighted means are calculated as the sum of each species extquotesingle cell abundances multiplied with their respective trait, divided by the total cell abundance. Relative Importance of eco-evolutionary changes to the total change are calculated following the formula given in Hattich et al 2022 (https://doi.org/10.1111/1365-2435.13923). Nutrients were measured at the end of the assay when most communities have reached stationary phase with a Autoanalyzer (Thermo Scientific Flash).